2009
DOI: 10.1080/09603100802243766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of wind on stock market returns: evidence from European markets

Abstract: Environmental psychology studies have found evidence that wind speed has a strong influence on mood and comfort. This study investigated the relationship between wind speed and daily stock market returns across 18 European countries from 1994 to 2004. A significant and pervasive wind effect was found on stock returns. This finding was supported by psychological literature claiming that mood affects judgement and decision-making in situations involving uncertainty and risk, and coincides with the argument of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 70 publications
(80 reference statements)
1
17
0
Order By: Relevance
“…Thus, this result provides theoretical support for the argument of empirical studies that improved investor mood increases asset prices (e.g. Saunders, 1993;Hirshleifer and Shumway, 2003;Krivelyova and Robotti, 2003;Kamstra et al, 2003;Yuan et al, 2006;Shu and Hung, 2009).…”
Section: Effects Of Varying Mood Factors On Asset Pricessupporting
confidence: 63%
See 2 more Smart Citations
“…Thus, this result provides theoretical support for the argument of empirical studies that improved investor mood increases asset prices (e.g. Saunders, 1993;Hirshleifer and Shumway, 2003;Krivelyova and Robotti, 2003;Kamstra et al, 2003;Yuan et al, 2006;Shu and Hung, 2009).…”
Section: Effects Of Varying Mood Factors On Asset Pricessupporting
confidence: 63%
“…Consequently, high geomagnetic activity is followed by negative stock returns while stock returns increase during periods of quiet geomagnetic activity. Similarly, temperature (Cao and Wei, 2005;Chang et al, 2006;and Keef and Roush, 2007) and wind (Keef and Roush, 2007;Shu and Hung, 2009) reportedly have a negative influence on stock prices.…”
Section: Evidencementioning
confidence: 95%
See 1 more Smart Citation
“…Plenty of empirical support can be found for the argument that weather impacts on the equity returns. Number of investigations has been carried out considering different weather factors such as number of sunshine hours (Shu and Hung, 2009), cloud cover, humidity levels (Shim et al, 2015), wind speed (Shu and Hung, 2009;Shim et al, 2015), raininess (Hirshleifer and Shumway, 2003) and temperature (Cao and Wei, 2005;Floros, 2008Floros, , 2011Shim et al, 2015) Cao and Wei (2005) examined the temperature anomaly in nine stock indices in eight equity markets in USA, Canada, Britain, Germany, Sweden, Australia, Japan and Taiwan using bintest and regression. The study revealed that there is a negative relationship between temperature and stock market returns.…”
Section: Weather and Equity Returnsmentioning
confidence: 99%
“…Psychological research has documented the effects of mood on decision-making process (Etzioni, 1988) and a good mood is associated with fast and efficient decision-making (Forgas, 1998). Saunders (1993), Hirshleifer and Shumway (2003), Krivelyova and Robotti (2003), Cao and Wei (2005), Chang, Nieh, Yang, & Yang (2006), Keef and Roush (2007), Shu and Hung (2009), and Gómez and Prado (2014) have shown empirical researches in behavioral finance that has accumulated different evidences. Said evidence shows how returns are related to mood variables.…”
mentioning
confidence: 99%